Perempuan dan Perlindungan Hukumnya Terhadap Diskriminasi Gender - Nafisah Amanda Anggraini Putri; Nabilla Carissa Davu; Muhammad Fariz Al Ghaza; Asep Suherman (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Gender discrimination against women remains a serious issue in Indonesia, both in public and domestic spheres. Although various legal instruments guarantee equality, social practices still reflect unequal treatment, marginalization, and gender-based violence. This study aims to analyze the forms of discrimination experienced by women and to evaluate the effectiveness of legal protection provided by the state. The research applies a normative juridical method with statutory and conceptual approaches. Primary legal materials include the 1945 Constitution, Law No. 7 of 1984 on the Ratification of CEDAW, and Law No. 23 of 2004 on the Elimination of Domestic Violence, while secondary materials are obtained from legal literature and academic journals related to gender equality. The findings show that although Indonesia’s legal framework recognizes the principle of equality, its implementation is still hindered by patriarchal culture, low legal awareness, and weak law enforcement. Affirmative policies, improved capacity of law enforcers, and active community participation are needed to create effective and fair legal protection for women.